Perancangan Desain User Interface dan User Experience Web APE Barbershop Menggunakan Figma Dengan Metode Human Centered Design (HCD) & Pengujian System Usability Scale (SUS) - Putra Hidayatullah (Tamilis Synex: Multidimensional Collaboration, 2025)
The development of digital technology requires service businesses such as barbershops to have an attractive, informative, and easily accessible online platform for users. A well-designed user interface (UI) and user experience (UX) play an important role in creating a first impression, increasing customer satisfaction, and loyalty. This study aims to design the UI/UX of the Ape Barbershop profile website using the Human Centered Design (HCD) approach and conduct usability testing with the System Usability Scale (SUS). The HCD method applied consists of three main stages, namely Inspiration, Ideation, and Implementation. At the Inspiration stage, observations and questionnaires are distributed to prospective users to explore the needs, preferences, and obstacles experienced when accessing barbershop information online. The Ideation stage produces a design of interaction flows, information structures, and UI elements based on the results of the user needs analysis. Furthermore, the Implementation stage realizes the website prototype and tests it on users using the SUS method. The test results show that the final design has a good level of usability with a SUS score of 85%, which is included in the "Excellent" category. This shows that the HCD approach is able to produce website designs that are in accordance with user needs and preferences. This study concludes that the application of HCD and evaluation using SUS is an effective combination in producing optimal UI/UX designs for web-based services such as barbershops.